THE ANALYSIS OF THE ATTITUDES OF TODAY'S STUDENTS PATRIOTISM - Elena Zritneva; Ekaterina Guz (Вестник Северо-Кавказского федерального университета, 2022)
In the article the philosophical, political, sociological and pedagogical positions discusses the concept of «patriotism». Shows the multiplicity and diversity of scientific approaches to the understanding ofpatriotism. The results of the empirical study and the analysis of the attitudes of contemporary students to patriotism, its perception as value. It is shown that patriotism is the basis of formation of national identity and a means of integration of the national community, evident in the active actions, based on the realization ofnational interests and the need to protect them.